Răspuns :
2x (1 nr.)
(1/4 * 2x) - 2 (al 2-lea nr.)
x (al 3-lea nr.)
Deducem și rezolvăm:
2x + (1/4 * 2x) - 2 + x = 418
2x + (x/2 - 2) + x = 418
2x + (x-4)/2 + x = 418
4x/2 + (x - 4)/2 + 2x/2 = 418
(4x + x - 4 + 2x)/2 = 418
(7x - 4 )/2 = 418
7x - 4 = 418 * 2
7x - 4 = 836
7x = 836 + 4
7x = 840
x = 840/7
x = 120
Obținem: 2 * 120 = 240 ( 1 nr.)
(1/4 * 2*120) - 2 = 60 - 2 = 58 (2 nr.)
120 ( 3 nr.)
Verificăm: 240 + 58 + 120 = 418
Sper că te-am ajutat, o zi bună și succes la învățătură))
(1/4 * 2x) - 2 (al 2-lea nr.)
x (al 3-lea nr.)
Deducem și rezolvăm:
2x + (1/4 * 2x) - 2 + x = 418
2x + (x/2 - 2) + x = 418
2x + (x-4)/2 + x = 418
4x/2 + (x - 4)/2 + 2x/2 = 418
(4x + x - 4 + 2x)/2 = 418
(7x - 4 )/2 = 418
7x - 4 = 418 * 2
7x - 4 = 836
7x = 836 + 4
7x = 840
x = 840/7
x = 120
Obținem: 2 * 120 = 240 ( 1 nr.)
(1/4 * 2*120) - 2 = 60 - 2 = 58 (2 nr.)
120 ( 3 nr.)
Verificăm: 240 + 58 + 120 = 418
Sper că te-am ajutat, o zi bună și succes la învățătură))